A fuzzy bi-objective MILP approach to integrate sales, production, distribution and procurement planning in a FMCG supply chain - Nemati, Yaser; Alavidoost, Mohammad Hosein (Soft computing (Berlin, Germany), 2019)
Sales and operations are the heart of today’s businesses, and the decisions made in these areas will intensively affect the financial performance, operational efficiency and service level of the whole organization. This manuscript is going to develop three multiobjective fuzzy mixed integer linear programming models of sales and operations planning process. Then, the performance of the fully integrated fuzzy model is compared to the similar crisp model, in terms of total supply chain’s cost and customer service level. All the models are developed for a multisite manufacturing company, which is coping with different raw material suppliers and third-party logistics, distribution centers and customers with a wide range of product families. Finally, the models are applied to a real case in a FMCG manufacturing company in Iran. The final results approve the superiority of the fuzzy model over the crisp one. Furthermore, a sensitivity analysis is carried out to analyze the effect of some key factors on the benefits of the SC planning integration.